Penerapan Dimensi Akuntabilitas pada Yayasan Murni Pendidikan Sosial "Sunan Drajat" Lamongan - Khoirul Wakhid; Rohmawati Kusumaningtias (Muttaqien, 2025)
The purpose of this study was to determine the application of the accountability dimension to the "Sunan Drajat" Lamongan Social Education Pure Foundation. The research used is qualitative research with interpretive methods. Data collection techniques used are through interviews and observation. Data processing was carried out in a qualitative description. The results of this study indicate that the Pure Social Education Foundation "Sunan Drajat" Lamongan has implemented accountability dimensions including honesty and legal accountability managerial accountability, program accountability, policy accountability, financial accountability. However, there are several dimensions of accountability that have not run optimally. First, in honesty and legal accountability, it is explained that in foundations there are no concurrent positions but sometimes there are concurrent duties by administrators. This occurs because the presence of administrators is not fully in accordance with the existing management structure. Second, related to policy accountability, it is explained that the foundation already has policies related to strategic plans, but has not set a timeline for achieving targets for each policy that has been formulated. Third, in terms of financial accountability at the foundation, when viewed in terms of financial statements, it is still relatively simple in the form of cash flow, and is not fully in accordance with PSAK No. 45